Enzymolytic soybean meal—impact on growth performance, nutrient digestibility, antioxidative capacity, and intestinal health of weaned piglets - Tan, Kai; Bian, Zhiyao; Liang, Huiqing; Hu, Wenyue; Xia, Miao; Han, Shuaijuan; Chen, Baojiang (Frontiers in Veterinary Science, 2024)
Enzymolytic soybean meal (ESBM) enriches free amino acids and small peptides, while mitigating anti-nutritional factors. Substituting soybean meal with ESBM enhances animal performance, though optimal piglet dietary supplementation levels vary. The present study aimed to assess the impact of ESBM on the growth performance, nutrient digestibility, antioxidative capacity and intestinal health of weaned piglets. A total of 120 piglets (initial body weight, 7.0 ± 0.4 kg) were randomly allocated into 4 dietary groups, each comprising 5 replicates with 6 piglets per replicate. The control group received the basal diet, while the experimental groups were fed diets containing 2, 4% or 8% ESBM as a replacement for soybean meal over 28 days. Compared with the control group, piglets supplemented with 4% ESBM exhibited a significant increase (p < 0.05) in average daily gain and the apparent total tract digestibility of dry matter, ether extract and gross energy (p < 0.05), alongside a notable decrease (p < 0.05) in diarrhea incidence. Fed ESBM linearly increased (p < 0.05) the villus height in the ileum of piglets. The levels of superoxide dismutase and total antioxidant capacity in serum of piglets increased (p < 0.05) in the 2 and 4% ESBM groups, while diamine oxidase content decreased (p < 0.05) in the 4 and 8% ESBM group. ESBM inclusion also upregulated (p < 0.05) the expression of superoxide dismutase 1 (SOD-1), Catalase (CAT) and claudin-1 mRNA. In terms of cecal fermentation characteristics, ESBM supplementation resulted in a increase (p < 0.05) in valerate content and a linear rise (p < 0.05) in propionate, butyrate, and total short-chain fatty acids levels, accompanied by a decrease (p < 0.05) in the concentrations of tryptamine and NH3 in cecal digesta. ESBM had no discernible effect on cecal microbial composition. In summary, substitution of soybean meal with ESBM effectively improved the growth performance of piglets by enhancing nutrient digestibility, antioxidant capacity, intestinal barrier and cecal microbial fermentation characteristics, with the optimal replacement level identified at 4%.